Critical and effective histories : Foucault's methods and historical sociology - Dean, Mitchell, 1955- (Routledge, 1994)
Critical and Effective Histories contrasts Foucault's methodologies with central currents in social theory and philosophy. It provides a guide to doing historical sociology, and an original position on the condition of social science today.